Pengamanan Data User Login dengan Algoritma Kriptografi Tea dan Notifikasi SMS - Siswanto Siswanto; M. Anif; Ulil Abshor (Ikatan Ahli Informatika Indonesia, 2018)
Application of user login data security is designed to secure user login user data at PT. TELKOM Indonesia TBK, HSI Division in Minitools application containing data from customer's internet number. The security of user logni data is very vulnerable to the theft of various irresponsible parties that will impact on the manipulation of customer data in the Minitools application. These problems can be encountered by adding applications to prevent irresponsible parties from being able to read passwords from user login data in the database. In addition, by adding SMS notification feature to prevent irresponsible parties are free to use user login data to access and change customer data on Minitools application. In this paper the algorithm used in cryptography, the cryptography algorithm Tiny Encryption Algorithm (TEA). For SMS notification itself, built using Gammu module as a special software aids SMS Gateway, PHP, and also Wavecom GSM M1306B modem. The result of this cryptographic testing, password data can be secured in the form of text encrypted (ciphertext). With the application of data security user cryptographic login and SMS notification for this login system will make the information system more secure because the password will be encrypted and the authentication code to login to the application Minitools sent to the user's mobile number. From the experimental results, the average duration of the encrypt process is 0.08361488 ms and the duration of the descrypt process is 0.166120556 ms. For the average sms the duration is not more than 10 second.